An examination of validation practices in relation to the forensic acquisition of digital evidence in South Africa - Jordaan, Jason (Rhodes University, Faculty of Science, Department of Computer Science, 2014)
The acquisition of digital evidence is the most crucial part of the entire digital forensics process. During this process, digital evidence is acquired in a forensically sound manner to ensure the legal admissibility and reliability of that evidence in court. In the acquisition process various hardware or software tools are used to acquire the digital evidence. All of the digital forensic standards relating to the acquisition of digital evidence require that the hardware and software tools used in the acquisition process are validated as functioning correctly and reliably, as this lends credibility to the evidence in court. In fact the Electronic Communications and Transactions Act 25 of 2002 in South Africa specifically requires courts to consider issues such as reliability and the manner in which the integrity of digital evidence is ensured when assessing the evidential weight of digital evidence. Previous research into quality assurance in the practice of digital forensics in South Africa identified that in general, tool validation was not performed, and as such a hypothesis was proposed that digital forensic practitioners in South Africa make use of hardware and/or software tools for the forensic acquisition of digital evidence, whose validity and/or reliability cannot be objectively proven. As such the reliability of any digital evidence preserved using those tools is potentially unreliable. This hypothesis was tested in the research through the use of a survey of digital forensic practitioners in South Africa. The research established that the majority of digital forensic practitioners do not use tools in the forensic acquisition of digital evidence that can be proven to be validated and/or reliable. While just under a fifth of digital forensic practitioners can provide some proof of validation and/or reliability, the proof of validation does not meet formal international standards. In essence this means that digital evidence, which is preserved through the use of specific hardware and/or software tools for subsequent presentation and reliance upon as evidence in a court of law, is preserved by tools where the objective and scientific validity thereof has not been determined. Since South African courts must consider reliability in terms of Section 15(3) of the Electronic Communications and Transactions Act 25 of 2002 in assessing the weight of digital evidence, this is undermined through the current state of practice in South Africa by digital forensic practitioners.
Keywords: Electronic evidence; Evidence, Criminal; Forensic sciences; Evidence, Criminal -- South Africa -- Law and legislation